Factors affecting the turnover intention among employees in Penang manufacturing industry - Tin Phang Ooi; Kok Ban Teoh (Annals of Human Resource Management Research, 2021)
Purpose: The objective of the present study is to examine how work engagement, job demands and organizational commitment affect turnover intention among employees in Penang manufacturing industry. Research Methodology: Quantitative approach will be used in this study by distributing the online questionnaire to collect data from a sample of 75 employees drawn from manufacturing companies in Penang, Malaysia. Results: The present study found out that work engagement and job demands have no significant relationship with turnover intention. Besides, the present study indicates that organizational commitment is negatively related to turnover intention. Limitations: In this research, only 75 employees from Penang manufacturing industry had participated in the study. Since this small number of employees could not represent the entire Malaysia population, the future research should expand to involve a bigger sample of employees from Malaysia manufacturing industry to collect more reliable results. Contribution: The findings of this research provide benefits to the Federation of Malaysian Manufacturing (FFM) and manufacturing companies as they can understand the devastation effects of turnover and be equipped with strategies to decrease the turnover rate. Keywords: Employee, Job demands, Manufacturing industry, Organizational commitment, Turnover intention, Work engagement